Hidroponik Wick System Sebagai Alternatif Budidaya Sayur-Sayuran di Wilayah Pesisir Desa Laikang Kabupaten Takalar - Ilman Hidayat; Nurazizah Nurazizah; Muhammad Fahri Wahyudi; Nur Fitri Ramadhani; Andini Andini; Nunik Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Laikang village is the villages on the coast with a sandy and marginal soil environment, so it is not suitable for vegetable cultivation. The hydroponic wick system technology allows people in Laikang Village to be able to cultivate vegetables in their own yard. This community service aims to provide training on vegetable cultivation and how to make a hydroponic wick system by utilizing plastic bottle waste. This activity is carried out in 3 stages, namely the survey and socialization stage, the training stage, and the monitoring and evaluation stage. From the evaluation, there is an increase in the knowledge and skills of the participants regarding the theme of the activity. The evaluation results also showed that the implementation of this activity was in accordance with community expectations, with the level of satisfaction of training participants at 87%, participants' interest in the training theme at 89%, and the level of conformity with community expectations at 82%. The results of monitoring activities also show the continuity of cultivation activities that are still occupied by the people of Laikang Village to this day.